Cama de frango e organomineral na cultura da cana-de-açúcar - Ramos, Lucélia Alves (2013)
Sugarcane fertilization takes a fundamental role in the whole production process, affecting the crop directly and indirectly. The use of organic residues as nutrient sources can be an alternative for substituting or complementing mineral fertilization for the crop. Therefore, this study determined the effect of poultry litter, organomineral and mineral fertilizers on sugarcane yield, technological variables, soil chemical properties and leaf nutrient contents, both in plant and ratoon cane. Two experiments were done in a commercial field at Jalles Machado Mill, in Goianésia, GO, from July 2009 to April 2010. Both areas received, in September 2009, in the furrows, the following treatments: Standard mineral fertilization of the Mill - 66 kg ha-1 N: ammonium nitrate (NH4NO3 - 34% N); 120 kg ha-1 P2O5: mono-ammonium phosphate (MAP - NH4H2PO4 - 54% P2O5); 82 kg ha-1 K2O: potassium chloride (KCl- 60% K2O) which was considered as an additional treatment; poultry litter or organomineral compost at the doses 3.0, 6.0 and 9.0 t ha-1, besides a control without any of the treatments. The experimental design was randomized blocks, as a 2 x 3 + 1 + 1 factorial, two fertilizers (poultry litter or organomineral compost) x three doses + one additional treatment (mineral fertilization) + one control treatment, with four replications. Five months after treatment application, for both areas, 20 leaves per plot were collected and used for analysis of macronutrients (N, S, K, P, Ca and Mg) and micronutrients (Fe, Mn, Cu and Zn). Harvest was done nine months after treatment application and the stalks weighed to determine yield, and soil was collected at the depths 0-20 and 20-40 cm for analysis of pH, Ca, Mg, P, K, and Al contents and organic matter. Also, ten plants were arbitrarily collected in the center row of each plot in each área, for technological analysis (juice brix, cane fiber, juice and cane pol and purity of juice and cane). Plant cane yield was greater with the use of poultry litter and organomineral compost than with mineral fertilization. Organomineral compost was better than poultry litter in increasing yield of plant cane, resulting in a linear yield increase of plant cane up to 9 t ha-1 of the former. Ratoon cane yield was similar with all three fertilizers. Soil phosphorus contents increased in plant and ratoon cane after fertilization with poultry litter and organomineral compost. The use of poultry litter, organomineral compost or mineral fertilizer did not change sugarcane technological variables, nor soil P, K, Ca and Mg contents, acidity and organic matter, nor leaf nutrients.